The Effect of Ethical Climate on Whistleblowing Intention with Ethics Training as a Moderating Variable - Antoh, Alfiana (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyse the effect of organisational ethical climate and ethics training on whistleblowing intentions of local government accounting staff based on the Ethical Climate Theory proposed by Victor and Cullen (1988), as well as the moderating effect of ethics training on the relationship between ethical climate and whistleblowing intentions. Using data collected through a questionnaire survey with direct mailing method to 63 employees working in the accounting and assets department in the Regional Financial Management Agency in 3 regencies/cities in Papua Province, Indonesia. This study found that ethical climate and ethics training influence whistleblowing intentions. However, ethics training did not strengthen the relationship between ethical climate and whistleblowing intentions. These findings support the Ethical Climate Theory. Practically, this study suggests that increasing whistleblowing intentions by LG accounting staff can be achieved by improving the ethical climate within the organisation and supporting accounting staff to attend ethics training.